Peningkatan Kreativitas dan Hasil Belajar Mata Pelajaran Bahasa Indonesia pada Materi Pembuatan Poster bagi Siswa melalui Project Based Learning - Puspitarani, Vidya; Sayekti, Ika Candra; My Stiyani, Dwi Fuji (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research is motivated by the suboptimal learning process, resulting in low creativity among students, which affects the outcomes of Indonesian language subjects, particularly in poster making. The study aims to enhance creativity and learning outcomes in Indonesian language through poster making using project-based learning approach. The method employed is Classroom Action Research with two cycles, encompassing planning, implementation, data collection, and reflection. The research subjects are 27 sixth-grade students at SD N Kleco 1. Data collection is conducted through assessment of poster creativity and learning outcome tests. Through the implementation of Classroom Action Research with project-based learning approach, students' creativity and learning outcomes significantly improve from one cycle to another. Student creativity increases from 40% in the pre-cycle to 57% in cycle I and 81% in cycle II, with the average score rising from 56 in the pre-cycle to 70 in cycle I and 79 in cycle II. The increase in learning outcomes occurred due to students' curiosity about the material which was dominated by projects in learning.